Caracterização de sistemas lacustres no Município de Boa Vista, Roraima - Munhoz, Rodrigo (2020)
The fields of the Branco River, where the municipality of Boa Vista is located, have a vast set of lakes divided into different systems, strongly influenced by the seasonality of the local climate and of great scenic beauty. This work aims to characterize the different lake systems. For this purpose were realized sediment samples were collected from the bed and photographs were taken of four lakes located in different systems, geoprocessing and photo-interpretation of Landsat 8 images, one from the wet period (which occurs between April and September) and the other from the dry period (which occurs between October and March), the construction of maps, granulometric analyzes of the collected sediments and bibliographic review of authors who analyzed different systems within the municipality. The presence of six different lake systems in Boa Vista was found and the lakes were of four types according to the classification criterion by origin of their forming depressions: tectonic, wind, fluvial and organic. All systems are seated on the upper layer of the Boa Vista Formation and have clear sediments from acidic rocks, consistent with the material of this formation. However, the lakes of the Apoteri Volcanic Rock Complex also have reddish-orange material, poorly selected and lateritic concretions, resulting from the alteration of the basic rocks of the complex. Most lakes are still oriented in the L-O or NE-SO directions, showing structural control and / or influence of the prevailing local winds.